Odpowiedź:
Szczegółowe wyjaśnienie:
A
d)2x+[tex]x^{2}[/tex] dla x=4
2*4+[tex]4^{2}[/tex]
8+16
24
e)[tex]p^{2} -p^{3}[/tex] dla p=2
[tex]2^{2}-2^{3}[/tex]
4-8
-4
B
d)[tex]3x^{2} +2x[/tex] dla x= -1
[tex](-1)^{2}[/tex]+(-1)*2
1-2
-1
e)[tex]\frac{-7}{8-4a}[/tex] dla a= -1
[tex]\frac{-7}{8-4*(-1)}[/tex]
[tex]\frac{-7}{8+4}[/tex]
[tex]\frac{-7}{12}[/tex]
C
e)3mn+[tex]m^{2}[/tex]n dla m=2 n= -6
3*2*(-6)+[tex]2^{2}[/tex]*(-6)
-36-24
-60
d)[tex]\frac{4}{t+3s}[/tex] dla t= -3 i s= -2
[tex]\frac{4}{-3+3*(-2)}[/tex]
[tex]\frac{4}{9}[/tex]